Transforming Customer Experience in Petro Retailing: Adapting to Emerging Trends and Expectations - Purohit, Santanu; Purohit, Sujoita; Jain, Arvind Kumar (Business, Management and Economics: Research Progress Vol. 9, 2024)
Customer experience plays a vital role in the service industry, and it is becoming important daily. With the broad exposure of technological advances, Indian customers' behaviour is changing to value their money. The retail fuel market is undergoing significant disruption, driven by several transformative trends reshaping the industry globally. One of the most impactful shifts is the rise of alternative energy sources, such as renewables and electric power. Alongside this, emerging mobility models like shared transportation are gaining traction while customer expectations continue to evolve toward convenience and personalisation. Today's consumers demand a tailored experience where products and services are customised to meet their specific needs. The study aimed to identify the drivers that influence Indian petro retail customers' experience and evaluate them according to their prominence, based on the degree of influence on customer experience. The study was conducted from September – to November 2021 and was shown at various fuel stations in Mumbai (Metro) and Ranchi (non-metro). The sample scope selected for the study was 400 for each city. In this rapidly changing landscape, digital technology is poised to play a central role in driving innovation and competitive advantage. As these shifts unfold, they will fundamentally alter the market's competitive dynamics, necessitating a transformation of the traditional business model. With advancements in technology, customer buying behaviour has also evolved, and this change highlights the need to re-evaluate the factors influencing the customer experience. Identifying and validating these evolving drivers has become crucial for businesses to remain relevant and competitive. The study concluded that five key drivers significantly impact customer experience at fuel stations. Staff behaviour, speed of service, the station's appearance, and the payment process all play vital roles in shaping a positive customer-fueling experience.